Beda Arti Firman "Bacalah" dalam Pendidikan Islam-Kristen (Rekonstruksi Teks Baca-Tulis Dalam Pembelajaran) - Farida Asy’ari (Eksos, 2019)
Prompts for "reading" actually existed since when the revelation of God was revealed for the first time received by the prophet Muhammad SAW. In Holly Bible the book of Christians reveals that in the tradition of the Jewish command "Reading" after there is a book and reading to understand history and law. So before "reading" must do writing first. Thus, according to them, that the word of God "read" contained in his book is meaning "writing", which this thing is written directly in the book of output 17: 14 who was ordered to write history, and the book of Deuteronomy 4: 13-14 where God write 10 commands and teach commands. This research was conducted to find out and reveal the different meanings of the word "read" in Christian-Islamic Education. "Read-write" Text correlation in learning. The research method used is a theoretically oriented qualitative approach is a way of looking at the world, the assumptions that people embrace about something important, and what makes people work. So that the meaning of the word "read" in Islamic education means "reading" based on the word of God which first came down to the Prophet Muhammad, namely 'Iqra' in the letter Al-Alaq. Whereas in Christian education means "writing". Based on the word of God to the Prophet Moses in the book EXPLANATION 17: 14 in the Torah or the old agreement. The difference, the author tries to combine that reading and writing is a unity that cannot be separated in an education and learning. Therefore read-write that was not respected and preserved in learning must be rebuilt for the advancement of students as the nation's successor.